Teachers' Efforts in Fostering Students' Interest in Reading During the Covid-19 Pandemic in Class III Elementary School: Upaya Guru Dalam Menumbuhkan Minat Baca Peserta Didik Pada Masa Pandemi Covid-19 di Kelas III Sekolah Dasar - Siti Faisyah; Feri Tirtoni (Academia Open, 2021)
This study aims to determine the reading interest of students during the covid-19 pandemic in class III SDN Gempol Klutuk and the teacher's efforts in fostering student interest in reading during the covid-19 pandemic in class III SDN Gempol Klutuk. The subjects of this study were principals, teachers, guardians and third grade students of SDN Gempol Klutuk. This study uses a descriptive qualitative approach with case study research methods with data collection techniques in the form of questionnaires, interviews and documentation. The results of this study indicate that the low reading interest of third grade students at SDN Gempol Klutuk during the Covid-19 Pandemic, as well as the teacher's efforts to minimize the low interest in reading of students during the Covid-19 Pandemic.